Pendampingan Pentingnya Strategi dalam Meningkatkan Minat Nasabah terhadap Investasi Saham di Surabaya - Lestari, Veronika Nugraheni Sri; Cahyono, Dwi; Azah, Nila Romatal; Ariyanti, Devy Mei (LP3M STAI Darussalam Krempyang Nganjuk, 2020)
Capital markets are often interpreted as a market for a long-term financial instrument (securities) (its maturity is more than 1 year). In addition to that understanding, the capital market is also often associated as a place for the transaction of the party that needs funds (the company) and the Excess party (financier). The initial step of Sharia capital market developments in Indonesia began with the issuance of sharia funds on 25 June 1997 followed by the issuance of sharia bonds at the end of 2002, followed by the presence of the Jakarta Islamic Index (JII) in July 2000. The marketable securities traded on the stock exchange include stocks, bonds and mutual funds. Marketable securities are often referred to as ' financial instruments ' or ' securities ' or ' Sekuritas ' (Securities Act No. 8 year 1995 defines the capital market as